(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Background: The orphan status of sickle cell invites many researchers toward drug development in the past decade. A substantial number of clinical trials either understudies or in the planning stage focused on sickle cell disease. Sickle cell traits are often considered asymptomatic and the silent condition is associated with diverse complications. Objective: To clinically evaluate the safety and effectiveness of T-AYU-HM Premium Tablets (300mg) in sickle cell anemia patients: an observational retrospective study Methodology: This is a single-arm case-control retrospective study of sickle cell trait patients admitted to Dhanvantari Clinic from 2018 to 2020. Patients’ vital and clinical information based on inclusion and exclusion criteria were collected and analyzed using SPSS software. Result: A total of 100 patients with sickle cell traits were included in the study. The treatment exhibited significant improvement was seen in (P<0.05) in hemoglobin and red blood corpuscles. There wasn’t any untoward response either from the patient or from laboratory parameters reported indicating no adverse effects were seen. There was an absolute improvement in overall health as a reduction of no of time hospitalization (0) and blood transfusion (0) in sickle cell trait patients. There was a significant improvement in minor and major clinical parameters of sickle cell trait patients. Conclusion: The effect of T-AYU-HM Premium treatment in sickle cell trait patients suggests it is safe and effective. There was no adverse effect observed in the observational study. During entire study period, no single blood transfusion or hospitalization required. The significant improvement in the rate and frequency of painful crises indicates an improvement in pain-related quality of life in patients. This treatment of T-AYU-HM Premium was safe, cost-effective, and exhibit therapeutic potential in the management of sickle cell trait patients